ALAM BERKEMBANG MENJADI GURU (Nilai-Nilai Kehidupan Buya Hamka sebagai Sumber Pembelajaran Nilai di IPS) - Wildan Insan Fauzi; Yusuf Faisal Ali (Sosio-Didaktika: Social Science Education Journal, 2017)
Assessing the thinking of a character is one of the attempts to decipher history in the form of biography that is necessary as a value-based subject matter in social studies, which is historical consciousness and wisdom about how we should treat life. This article uses a historical approach to analyze Hamka's personality in his youth until he becomes chairman of the MUI. Hamka is known as a rhetorical figure, firm, flexible and independent mindeness. A flexible personality coupled with his charismatic figure, friendly, humble attitudes and names known to everyone make him acceptable to all. The character of Hamka and how the characters are formed are values that are very useful for students to understand in Social Studies.